1424 Two Sides of the Same Coin: Opposite Paths in Patients Treated with the Same Strategy. (October 2012) - Piedimonte, A; Podagrosi, M; Mercurio, R; Mosca, A; Caiazzo, AM; Vania, A
Abstract : DG(13 years), family-history hypertension(IA), dyslipidemia, CVD; MG(14 years), family-history IA, both Tanner IV. Different school conducts-integration (DG:restless-good, MG: good-problematic); 7h/day of sedentary, MG is solitary, DG wishes to be more social, trains( 6hrs/week) and walks. No breakfast; junk food, or absent(MG); lunch and dinner alone or in family(MG); extra-snacks; soft-drink≥1/day. Both do nutritional mistakes. Both get balanced hypocaloric diet(1350kcal/day) and are pushed into sport. Conclusions: At T0 DG seems in a worse situation: this prompts him to better comply, with a general improvement. MG ignores his health status, perpetuating incorrect lifestyles, showing deterioration, acquiring risk factors for MS (HDL-C, BP, W). Even with similar initial status and similar strategy for both, the totally different results stress the importance of patients' compliance, even if still unable to plan future.